Contribution of Plasmodium knowlesi to Multispecies Human Malaria Infections in North Sumatera, Indonesia - Inke, ND Lubis; Hendri, Wijaya; Munar, Lubis; Chairuddin P, Lubis; Paul C, Divis; Khalid, B Beshir; Sutherland, Colin J (Oxford University Press, 2017)
Background. As Indonesia works toward the goal of malaria elimination, information is lacking on malaria epidemiology from some western provinces. As a basis for studies of antimalarial efficacy, we set out to survey parasite carriage in 3 communities in North Sumatera Province. Methods. A combination of active and passive detection of infection was carried out among communities in Batubara, Langkat, and South Nias regencies. Finger-prick blood samples from consenting individuals of all ages provided blood films for microscopic examination and blood spots on filter paper. Plasmodium species were identified using nested polymerase chain reaction (PCR) of ribosomal RNA genes and a novel assay that amplifies a conserved sequence specific for the sicavar gene family of Plasmodium knowlesi. Results. Of 3731 participants, 614 (16.5%) were positive for malaria parasites by microscopy. PCR detected parasite DNA in samples from 1169 individuals (31.3%). In total, 377 participants (11.8%) harbored P. knowlesi. Also present were Plasmodium vivax (14.3%), Plasmodium falciparum (10.5%) and Plasmodium malariae (3.4%). Conclusions. Amplification of sicavar is a specific and sensitive test for the presence of P. knowlesi DNA in humans. Subpatent and asymptomatic multispecies parasitemia is relatively common in North Sumatera, so PCR-based surveillance is required to support control and elimination activities.